2002
DOI: 10.1016/s0093-691x(02)00922-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an acute energy deficit on the hormone profile of dominant follicles in dairy cows

Abstract: The effect of an acute energy deficit on the hormone balance of dominant follicles was studied in six normally-cycling, high-yielding Italian Friesian cows at 60 and 90 days after calving. At 60 days after calving, the cows, which had been fed according to their maintenance and production requirements, were synchronized and follicular fluid was collected from the dominant follicles under ultrasound guidance. At 90 days after calving, the same protocol was used on the same cows, which had been subjected to an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 31 publications
7
32
1
2
Order By: Relevance
“…These findings suggest that, at least to some extent, the vulnerable oocyte and granulosa cells are protected from too high and possibly toxic NEFA concentrations during the NEB in high-yielding dairy cows. Elevated NEFA concentrations in serum and in FF have also been described in heifers and lactating cows that were subjected to an acute dietary restriction (Comin et al 2002, Jorritsma et al 2003. Our results also demonstrate that OA, PA and SA are the three predominant free fatty acids both in serum and in FF.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings suggest that, at least to some extent, the vulnerable oocyte and granulosa cells are protected from too high and possibly toxic NEFA concentrations during the NEB in high-yielding dairy cows. Elevated NEFA concentrations in serum and in FF have also been described in heifers and lactating cows that were subjected to an acute dietary restriction (Comin et al 2002, Jorritsma et al 2003. Our results also demonstrate that OA, PA and SA are the three predominant free fatty acids both in serum and in FF.…”
Section: Discussionsupporting
confidence: 78%
“…Being the only practical approach, the model used in the present study revealed for the first time possible toxic effects of high intrafollicular NEFA concentrations on the developmental competence of bovine oocytes in vitro. Acute fatty acid mobilization caused by food restriction or reduced appetite (illness or lameness) later pp also involves a fast NEFA rise both in serum as well as in FF (Comin et al 2002, Jorritsma et al 2003. The present study demonstrates that even a very short (24 h) exposure to elevated NEFA levels just prior to ovulation can be detrimental to the developmental capacity of the pre-ovulatory oocyte.…”
Section: Discussionmentioning
confidence: 56%
“…Also Jorritsma et al (2003) and Comin et al (2002) described an increase in NEFA concentrations in FF due to an acute dietary restriction. However, in these studies no concentration gradients between serum and FF were mentioned, there is now enough evidence to conclude that the growing and maturing oocyte is directly exposed to the typical biochemical changes that occur in highyielding dairy cows early post partum.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence for NEFA uptake by the ovary as well as a strong correlation between the concentration of NEFA in plasma and the follicular fluid, which could explain possible harmful effects of NEFA on either granulosa cells or the oocyte [8][9][10]. Several studies confirmed the importance of fatty acids for embryo development, but our study indicates that their impaired metabolism and high concentration might lead to the follicular cyst formation.…”
mentioning
confidence: 54%